2014
DOI: 10.1371/journal.pntd.0003282
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase 9 Production by Monocytes is Enhanced by TNF and Participates in the Pathology of Human Cutaneous Leishmaniasis

Abstract: IntroductionCutaneous leishmaniasis (CL) due to L.braziliensis infection is characterized by a strong inflammatory response with high levels of TNF and ulcer development. Less attention has been given to the role of mononuclear phagocytes to this process. Monocytes constitute a heterogeneous population subdivided into classical, intermediate and non-classical, and are known to migrate to inflammatory sites and secrete inflammatory mediators. TNF participates in the induction of matrix metalloproteinases (MMPs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 51 publications
0
42
2
Order By: Relevance
“…These molecules contribute to necrosis and cell recruitment to the site of infection. Monocytes and macrophages are heterogeneous subpopulations, with killing, inflammatory, and regulatory profiles 34. Previous studies have shown a high frequency of monocytes with inflammatory profile in E-CL,14 and there is a direct correlation between the frequency of monocytes expressing toll-like receptor9 with ulcer size in CL 37.…”
Section: Discussionmentioning
confidence: 97%
“…These molecules contribute to necrosis and cell recruitment to the site of infection. Monocytes and macrophages are heterogeneous subpopulations, with killing, inflammatory, and regulatory profiles 34. Previous studies have shown a high frequency of monocytes with inflammatory profile in E-CL,14 and there is a direct correlation between the frequency of monocytes expressing toll-like receptor9 with ulcer size in CL 37.…”
Section: Discussionmentioning
confidence: 97%
“…Such exaggerated expression of MMP1 has been observed to contribute to tissue destruction and disease progression in a number of other clinical contexts, including progression of rheumatoid arthritis (Xu et al, 2015), chronic obstructive pulmonary disease, acute respiratory distress syndrome, sarcoidosis, and tuberculosis (Elkington and Friedland, 2006). The pro-inflammatory cytokine tumor necrosis factor (TNF), which characterizes human CL caused by L. braziliensis (Castes et al, 1993; Ribeiro-de-Jesus et al, 1998), could be contributing to exaggerated expression of matrix metalloproteinases (Campos et al, 2014; Lehmann et al, 2005). TNF is known to accelerate degradation of type I collagens by MMP-1 leading to their gradual loss in human skin (Agren et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…As we observed in CL lesions, there was an exaggerated expression of MMP1 following infection of macrophages in vitro . High levels of TNF are produced following infection of monocytes with L. braziliensis (Campos et al, 2014). Thus it seems likely that high levels of MMP1 associated with CL pathogenesis may be contributed to by a direct effect of the parasite on macrophage function.…”
Section: Discussionmentioning
confidence: 99%
“…12 Products secreted by monocytes during CL include TNF, chemokines (CXCL9, CXCL10, and CCL2), and metalloproteinase-9 (MMP-9), and some reports indicate the participation of TNF and monocyte-derived MMP-9 in tissue damage during leishmaniasis. 2,13,14 Herein, we evaluated the immune response from a patient with HIV and L. braziliensis coinfection and found mononuclear phagocytes infiltrating the lesion and production of TNF, CCL2, and MMP-9 at lesion site.…”
Section: Introductionmentioning
confidence: 99%